2022
DOI: 10.1101/2022.07.28.501815
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hypothalamic extraretinal photoreceptor Opsin3 regulates water balance, body temperature and motor activity

Abstract: Opsin 3 (Opn3) is a light-sensitive protein present throughout the mammalian brain, although its functions in this organ are currently unknown. Since Opn3 encoded mRNA increases in the supraoptic nucleus (SON) of the hypothalamus in response to hyperosmotic stimuli, we have explored the role of Opn3 in this nucleus. By in situ hybridization, we have demonstrated that Opn3 is expressed in neurones expressing both arginine vasopressin and oxytocin in the rat SON, suggesting that OPN3 functions in both neuronal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…We then explored the relationship between the transcriptomes and the proteomes of SONs in the basal condition. In order to generate a complete rat transcriptome, we generated a dataset which included the entire transcriptome determined by RNA-seq of Wistar Han ( 20 ) and Sprague Dawley ( 42 ) rats in basal conditions ( supplemental Fig. S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We then explored the relationship between the transcriptomes and the proteomes of SONs in the basal condition. In order to generate a complete rat transcriptome, we generated a dataset which included the entire transcriptome determined by RNA-seq of Wistar Han ( 20 ) and Sprague Dawley ( 42 ) rats in basal conditions ( supplemental Fig. S2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between basal transcriptomes and proteomes was examined by comparing the proteome output obtained in the present study in basal conditions with a complete rat transcriptome combining all the genes detected in previous SON transcriptomic analysis in Sprague Dawley ( 42 ) and Wistar Han ( 20 ) rats in basal conditions. We found that 14.846 genes are commonly expressed in both strains, while only 356 and 545 genes are uniquely expressed in the SON of Wistar Han and Sprague Dawley rats ( supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%